2019
DOI: 10.1002/jwmg.21776
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐Scale Habitat Selection by Breeding White‐Tailed Ptarmigan in Colorado

Abstract: Species distributions are influenced by climate and topography in alpine ecosystems, yet resource selection studies of alpine species are uncommon. Basic characteristics of habitats used by alpine‐endemic white‐tailed ptarmigan (Lagopus leucura) have been described to explain foraging behavior, morphology, and survival in many alpine regions; however, there is a lack of information about fine‐scale habitat selection for nesting and brood‐rearing, particularly in the southern extent of the species’ range. Few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…In areas where White-tailed Ptarmigan sympatrically overlap with Rock Ptarmigan (L. muta), they occur at higher elevations with marginal cover and vegetation structure (Wilson and Martin 2012), but they experience higher nest success and number of hatched young than Rock Ptarmigan Martin 2010, 2012).At our study sites, we found a negative correlation between relative elevation and shrub cover (Pearson r = -0.481). Although shrub cover was only weakly related to daily nest survival, ptarmigan preferentially select shrub cover when it is available (Spear et al 2020), and previous studies have reported higher nest success with shrub concealment (Wiebe and Martin 1998b). On average, we also expect that higher elevations may be associated with lower-quality territories in terms of shrub food and concealment availability, which could have negative effects on the body condition of ptarmigan hens and subsequent fitness (Robb et al 1992).…”
Section: Environmental Effectsmentioning
confidence: 76%
“…In areas where White-tailed Ptarmigan sympatrically overlap with Rock Ptarmigan (L. muta), they occur at higher elevations with marginal cover and vegetation structure (Wilson and Martin 2012), but they experience higher nest success and number of hatched young than Rock Ptarmigan Martin 2010, 2012).At our study sites, we found a negative correlation between relative elevation and shrub cover (Pearson r = -0.481). Although shrub cover was only weakly related to daily nest survival, ptarmigan preferentially select shrub cover when it is available (Spear et al 2020), and previous studies have reported higher nest success with shrub concealment (Wiebe and Martin 1998b). On average, we also expect that higher elevations may be associated with lower-quality territories in terms of shrub food and concealment availability, which could have negative effects on the body condition of ptarmigan hens and subsequent fitness (Robb et al 1992).…”
Section: Environmental Effectsmentioning
confidence: 76%
“…Foraging microhabitat selection has been largely investigated as a function of habitat characteristics and availability (Tsiakiris et al 2009 ; Belotti et al 2013 ; Eierman et al 2014 ; Spear et al 2020 ; Barras et al 2020 ; Korniluk et al 2021 ). Although it is generally assumed that a forager distribution occurs at the highest prey densities to maximise their intake rate (Holling 1959 ; Stephens and Krebs 1986; Zwarts and Wanink 1993 ; Wallace et al 2015 ; Roder et al 2020 ), there is evidence showing that the overlap between species occurrences and the distribution of key resources may be imperfect due to different constraints including habitat complexity (i.e., detectability; Martinez et al 2010 ; Müller et al 2012 ; Benoit-Bird et al 2013 ; Liu et al 2019 ), presence of predators (e.g., Brown 1988 ; Heithaus et al 2002 ; Clare et al 2023 ), density-dependent effects (Piersma 2012; DeRoy et al 2020 ), as well as limitation associated with the sampling methodology (e.g., Hunsicker et al 2011 ; Kuhn et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%